Gamified Learning: Comparative Analysis of Quizizz vs. Manual Methods on Enhancing Students' Long-Term Memory Retention - Ahmad Silmul Fuady; Faid Widyawan Ainur Rizky; Patra Yonan; Muhammad Rokib; Ahmad Yusup (Global Education Journal, 2025)
Rapid expansion of digital pedagogy has intensified scholarly concern regarding the persistence of long-term memory retention within increasingly technology-mediated learning environments, particularly as conventional paper-based assessments continue to demonstrate vulnerability to accelerated cognitive decay associated with the forgetting curve. This investigation explores the comparative effectiveness of Quizizz and manual assessment methods in strengthening longitudinal mnemonic retention among secondary-level learners. Employing a quasi-experimental nonequivalent control group design, the study involved 64 participants divided into experimental and control cohorts across a four-week instructional intervention, followed by a 14-day delayed post-test interval to measure sustained recall stability. Empirical data reveal statistically significant differences between groups during both immediate and delayed retention assessments, with the experimental cohort demonstrating superior delayed recall performance (t(62) = 8.14, p < 0.001) and achieving a 93.38% retention rate compared to 84.13% within the manual cohort. The findings elucidate how interactive retrieval cycles, immediate feedback systems, and competitive engagement structures facilitate stronger cognitive consolidation and mitigate memory deterioration over time. The study ultimately underscores the necessity of reconfiguring assessment practices from static measurement procedures into digitally responsive reinforcement mechanisms capable of sustaining durable intellectual retention within contemporary instructional design frameworks.